Vocabulary Learning Strategies Used by Junior High School Students - Kristin Natalina Nugraha Bakti (Indonesian Journal of English Language Studies (IJELS), 2017)
In language learning, mastery of vocabulary is crucial. However, in Indonesia, where English is taught as a foreign language, vocabulary is often taught incidentally and given little priority. Due to the importance of vocabulary, a comprehensive language learning strategy is needed. As an example, vocabulary-learning strategies (VLS) can facilitate the development of vocabulary. This study aims at investigating VLS used by junior high school students in learning English. The data were collected by using Schmitt’s vocabulary learning strategies questionnaire. The questionnaire consists of 31 statements administered to 50 junior high school students in the 8th grade at SMP N I Salatiga. Interviews were also conducted to obtain more information from the participants. The results show that the students choose practical, simple and fast strategies in learning vocabulary. Strategies such as checking if the word is also an Indonesian word, guessing the word’s meaning from the context, asking the teacher to give the definition, studying the word with their classmates, remembering the word by studying and paying attention to the word’s spelling, underlining the word, and using English media were frequently chosen in this study.